Bismuth doping of hydrogenated amorphous germanium thin films - Burmeister, F (2006)
The optoelectronic properties of Bi-doped hydrogenated amorphous germanium (a-Ge:H), with relative impurity concentrations [Nimp/NGe] ranging between 8 × 10− 6 and 5.5 × 10− 3, are reported. The incorporation of Bi produces small changes in the dark conductivity of a-Ge:H. For a three orders of magnitude change in impurity concentration the room-temperature conductivity changes by just one order of magnitude. Within this doping range no, or small, changes were measured in the values of the pseudo-gap, the Urbach energy, and the hydrogen content. The Fermi level always remains far from the conduction band edge, shifting by only 0.1 eV for the sample with the largest doping concentration. The main conclusion is that Bi is a very inefficient active donor in a-Ge:H. The likely reasons for such behavior are discussed.